2013
DOI: 10.1152/ajplung.00179.2013
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Kv1.5 expression in intrauterine growth retardation rats with exaggerated pulmonary hypertension

Abstract: Chronic hypoxia pulmonary hypertension (CH-PHT) in adulthood is likely to be of fetal origin following intrauterine growth retardation (IUGR). Oxygen (O2)-sensitive voltage-gated potassium channels (Kv channels) in resistance pulmonary artery smooth muscle cells (PASMCs) play an important role in scaling pulmonary artery (PA) pressure. Expression and functional changes of Kv channels are determined, in part, by embryonic development. We hypothesized that O2-sensitive Kv channels play an important role in exagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
0
26
1
Order By: Relevance
“…The primary activator of BK Ca is epoxyeicoatrienoic acid (EET); however, changes in the production of EET from arachidonic acid have not been addressed in models of developmental programming. The involvement of other potassium channels, such as the voltage-gated potassium channel (K V ), was reduced in the pulmonary arteries from rat offspring of nutrient restricted dams, while the K Ca and inward-rectifying potassium channels (K IR ) were unaltered (240). In other studies, EDH contribution to vasodilation was maintained in rat offspring of hypoxic dams while the involvement of myoendothelial gap junctions increased in females but not males (265,266).…”
Section: Vasodilator Mechanismsmentioning
confidence: 85%
See 1 more Smart Citation
“…The primary activator of BK Ca is epoxyeicoatrienoic acid (EET); however, changes in the production of EET from arachidonic acid have not been addressed in models of developmental programming. The involvement of other potassium channels, such as the voltage-gated potassium channel (K V ), was reduced in the pulmonary arteries from rat offspring of nutrient restricted dams, while the K Ca and inward-rectifying potassium channels (K IR ) were unaltered (240). In other studies, EDH contribution to vasodilation was maintained in rat offspring of hypoxic dams while the involvement of myoendothelial gap junctions increased in females but not males (265,266).…”
Section: Vasodilator Mechanismsmentioning
confidence: 85%
“…An increased occurrence of aortic internal elastic lamina defects was also observed in offspring of bilateral uterine artery ligation rats (299). Vascular remodeling has been observed in the pulmonary arteries, where maternal nutrient restriction led to increased smooth muscle thickness following acute (240) or chronic (375,445) exposure of the offspring to hypoxia. Furthermore, the mesenteric arcade smooth muscle content was increased in a maternal undernutrition model (200).…”
Section: Vascular Remodelingmentioning
confidence: 87%
“…Additionally, antagonism of PDE5 with sildenafil promoted pulmonary vascular development and alveolarization, ostensibly via activation of the phosphatidylinositol-4,5-bisphosphate 3-kinase/Akt/mammalian target of rapamycin pathway and enhanced HIF-1␣ and HIF-2␣ activity (270). Other candidate regulators of lung vessel cell behavior have also been identified in vitro, including heat-shock protein 70 (5), the oxygen-sensitive voltage-gated potassium channel Kv1.5 (202), and AMPK (330); however, a role for these molecules in pulmonary vascular development awaits clarification.…”
Section: Pulmonary Vascular Development and Pphnmentioning
confidence: 99%
“…While acute hypoxia acts via inhibition of Kv channel activity, during chronic hypoxia K + channel density and Kv channel protein expression (Kv1.5 and Kv2.1) is decreased, although a Kv current is still detectable (124). However, both induction and repression of Kv channel subunit expression under chronic hypoxia has been described (44, 61,91,147). Patch clamp studies showed that the hypoxic inhibition of the Kv current in PASMC is unchanged even after 2 days of ambient hypoxia, when HPV is already lost (169).…”
Section: Voltage-gated K + Channelsmentioning
confidence: 99%